Bioengineered GelMA Tooth Bud Constructs for Future Applications in Regenerative Dentistry - Smith, Elizabeth. (2018)
Abstract: Tooth loss is a prevalent disease that affects millions of people worldwide. Loss of natural teeth can contribute to physiological and social disadvantages while reducing the quality of life. The exciting emerging field of Regenerative Dental Research aims to use biologically-based tissue engineering techniques to create bioengineered dental tissue and whole tooth replacement therapies. This innovative approach will provide function and responsiveness similar to natural teeth and serve as an alternative to currently used artificial materials. The basic goal of tissue engineering is to repair or replace damaged or lost tissues by utilizing a combination of cells and supportive scaffolds. The work described here is focused on the characterization and optimization of a three-dimensional (3D) tooth bud model composed of postnatal dental progenitor stem cells and HUVECs encapsulated within Gelatin Methacryloyl (GelMA) hydrogel scaffold. Preliminary in vitro results showed that GelMA hydrogels can be tuned to resemble mechanical characteristics of the natural tooth bud microenvironment. Also, encapsulated dental cells and HUVECs exhibited increased attachment, metabolic and MMP activities overtime. Furthermore, in vitro capillary-like networks formed within the 3D tooth bud model. In vivo implanted tooth bud constructs demonstrated functional vascular networks that circulated host red blood cells (RBCs) and mineralized tissue that adopted the size and shape of the original construct. Optimization of the GelMA tooth bud model aimed to assess the effect of various cell seeding densities and fabrication techniques. Optimized tooth bud constructs showed evidence of many features of natural tooth buds. This includes a putative dental epithelial stem cell (DESC) niche, a basement membrane, Wnt signaling, bioengineered enamel knot (EK) signaling center, transit amplifying (TA) cells, and fibrillin expression that resembled that of early tooth development. These results are the first to report the recapitulation of the natural DESC niche and other features of natural tooth development using postnatal dental cells. All of the results presented here, suggest that GelMA hydrogel is a promising scaffold material that can be used in future applications for bioengineering dental tissues and excitingly, whole teeth replacements in humans. Future studies focus on advancing this 3D tooth bud model towards clinical applications.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisors: Pamela Yelick, and Li Zeng.; Committee: Heber Nielsen, and Lauren Black III.; Keywords: Developmental biology, Cellular biology, and Histology.